The influence of sintering temperature on the structure, optical and magnetic properties of Yttrium iron oxide YFeO3 prepared via Lα-alanine assisted combustion method. Issue 11 (1st August 2017) - Al-Hazmi, F.S.; Al-Ghamdi, A.A.; Bronstein, L.M.; Memesh, Leena S.; Shokr, F.S.; Hafez, M.
Abstract: Single-crystalline YFeO3 nanoparticles with orthorhombic perovskite structure were synthesized via Lα -alanine assisted combustion approach. The effect of sintering temperature on the lattice and distortion parameters of the YFeO3 was discussed. The increase of the sintering temperature increased the lattice parameters and crystallite size, while decreased spontaneous strain, cell distortion, orthorhombic distortion and global instability factors. The sintering temperature did not show any significant effect of the atomic percentage of the elemental compositions of the YFeO3, where the powders showed excellent stoichiometry preserving the Y:Fe ratio (1:1). SEM micrographs showed that the YFeO3 powders exhibited quasi-rectangular shape. The magnetic properties showed an improvement of the remnant magnetization and coercivity with increasing the sintering temperature, owing to the decrease of distortion of orthorhombic perovskite structure. The diffuse reflectance UV–vis spectrophotometer was employed to investigate the optical behavior and band gap of the sintered YFeO3 powders at different temperatures. It was noticed that the reflectance bands are blue shifted and the optical band gap is decreased from 2.02 to 1.44 eV. This will gave rise to the possibility to use the developed YFeO3 orthoferrites as magnetic recoverable catalyst.